Description of Phaeobolaaeris gen. nov., sp. nov (Rhizaria, Cercozoa, Euglyphida) Sheds Light on Euglyphida's Dark Matter. (15th December 2020) - Dumack, Kenneth; Duckert, Clément; Meinhardt, Raphaela; Lara, Enrique; Bonkowski, Michael
Abstract: The majority of Euglyphida species are characterised by shells with imbricated silica scales. Environmental surveys indicate a large unexplored diversity and recent efforts hinted at a certain diversity of yet undescribed, inconspicuous, scale‐lacking Euglyphida. Here we describe Phaeobola aeris gen. nov., sp. nov. that shows a variety of morphological characters typical for the Euglyphida but lacks silica scales‐instead, this species bears an agglutinated test. Neither its morphology nor phylogenetic placement allows its assignment to any currently described family. We erected the yet monospecific genus Phaeobola gen. nov., which with yet available data remain Euglyphida incertae sedis .